2024
DOI: 10.1111/nmo.14777
|View full text |Cite|
|
Sign up to set email alerts
|

Avoidant/restrictive food intake disorder prevalence is high in children with gastroparesis and functional dyspepsia

Isha Kaul,
Helen Burton‐Murray,
Salma Musaad
et al.

Abstract: BackgroundAvoidant/restrictive food intake disorder (ARFID) prevalence in children with gastroparesis (Gp) and/or functional dyspepsia (FD) is unknown. We aimed to identify ARFID prevalence and trajectory over 2 months in children with Gp, FD, and healthy children (HC) using two screening questionnaires. We also explored the frequency of a positive ARFID screen between those with/without delayed gastric emptying or abnormal fundic accommodation.MethodsIn this prospective longitudinal study conducted at an urba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A large number of translations and adaptations of the NIAS have been made (e.g., Billman Miller et al, 2024;Fekih-Romdhane et al, 2023;He et al, 2021;Medina-Tepal et al, 2023;Van Ouytsel et al, 2024;Ziolkowska et al, 2022), including development of a parent-report version (Ziolkowska et al, 2022). The NIAS has also been used to examine the potential comorbidity of ARFID in individuals with gastrointestinal disorders, including gastroparesis, functional dyspepsia, achalasia, celiac disease, eosinophilic esophagitis, and inflammatory bowel disease (Burton Murray et al, 2020;Fink et al, 2022;Kaul et al, 2024;Robelin et al, 2021;Yelencich et al, 2022). However, several smaller clinical studies have now shown that the NIAS does not seem to differentiate well between ARFID and eating disorders driven by shape/weight concerns, because individuals with other eating disorders also have elevated scores on the NIAS (Billman Miller et al, 2024;Burton Murray et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of translations and adaptations of the NIAS have been made (e.g., Billman Miller et al, 2024;Fekih-Romdhane et al, 2023;He et al, 2021;Medina-Tepal et al, 2023;Van Ouytsel et al, 2024;Ziolkowska et al, 2022), including development of a parent-report version (Ziolkowska et al, 2022). The NIAS has also been used to examine the potential comorbidity of ARFID in individuals with gastrointestinal disorders, including gastroparesis, functional dyspepsia, achalasia, celiac disease, eosinophilic esophagitis, and inflammatory bowel disease (Burton Murray et al, 2020;Fink et al, 2022;Kaul et al, 2024;Robelin et al, 2021;Yelencich et al, 2022). However, several smaller clinical studies have now shown that the NIAS does not seem to differentiate well between ARFID and eating disorders driven by shape/weight concerns, because individuals with other eating disorders also have elevated scores on the NIAS (Billman Miller et al, 2024;Burton Murray et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of translations and adaptations of the NIAS have been made (e.g., Billman Miller et al, 2024; Fekih-Romdhane et al, 2023; He et al, 2021; Medina-Tepal et al, 2023; Van Ouytsel et al, 2024; Ziolkowska et al, 2022), including development of a parent-report version (Ziolkowska et al, 2022). The NIAS has also been used to examine the potential comorbidity of ARFID in individuals with gastrointestinal disorders, including gastroparesis, functional dyspepsia, achalasia, celiac disease, eosinophilic esophagitis, and inflammatory bowel disease (Burton Murray et al, 2020; Fink et al, 2022; Kaul et al, 2024; Robelin et al, 2021; Yelencich et al, 2022).…”
Section: Introductionmentioning
confidence: 99%